AN ANALYSIS OF EUPHEMISM IN ONLINE WRITTEN MASS MEDIA IN INDONESIA; JAKARTA POST AND REPUBLIKA NEWSPAPER IN POLITICAL SECTION - Erin Ernita Dewi; Khoirul Huda; Supriyatno Supriyatno (English Language Teaching Department (Prodi Pendidikan Bahasa Inggris), 2019)
Euphemism exists since there is an emergance of taboos and people nowadays are likely to avoid something harsh to say or mentioned. Further, the purpose of Euphemism in People’s communication is actually to maintain their social relation. Since Euphemism is very crucial in buildding up someone’s communication so that, it makes the researcher conducted this study of analysis Euphemism especially in Political field. Further, the aim of this research is to find out: (1) the types and functions of Euphemism appeared in Online Newspapers; Jakarta Post and Republika, (2) the most frequent of type and function of Euphemism have showen up in the selection section, Politics. Moreover, this research is qualitative-descriptive since the reasearcher analyzed the data interpretatively or based on the writers’ point of view. In addition, all the data explained descriptively by using some theories in describing the types and the functions of Euphemism. In categorizing the types, the researcher used theory from Allan and burridge who proposed 13 types of Euphemism and for explaining the function the researcher used Samoskaite theory who proposed 5 pragmatic functions of Euphemism. Moreover, the techniques in collecting the data the researcher followed 3 steps from Wray and Bloomer theory; choosing the media, transcripping the section and taking a note for the object (Euphemism). The last for analyzing the data there are 3 steps taken from Miles and Huberman theory; reducing data, displaying data, drawing and veryfying conclusions. In two weeks of the observation, the researcher found 9 Euphemism from 23 articles selected and 9 of them are categorized into 5 from 13 types Euphemism, they are; Figurative (Idiom and Irony), Circumlocution, Omission (Synecdoche), Understatement and Borrowing type. Further, the function of Euphemisms found in the Political section is categorized into Politeness function, Taboo function, and Tactical function. Finally, the researcher took a conclusion on the most frequent of type and function of Euphemism found in Online Newspapers; Jakarta Post and Republika in Political section published in April 10th to 23rd, 2019,and they are Idiom in figurative type and Taboo function.